CFD Analysis: Double Pipe Heat Exchanger, Latent Heat Storage, and BIM-CFD Integration - Vaishnavi Kaje; Satyam Shah; Kulkarni Shirish Prabhakarrao (International Journal of Electrical Machine Analysis and Design, 2024)
This is a review work covering four research papers. Heat exchangers transport thermal energy across fluids; research in SolidWorks 2014 compared flow simulation to the effectiveness-NTU approach. Slow PCM charging/discharging is a global concern in latent heat storage; research on the influence of flow rate and temperature on melting and solidification durations discovered efficiency in a triple tube heat exchanger design. Advances in computational fluid dynamics for forecasting separated flows in aircraft design are also presented. Designing and analysing heat exchangers, storage systems, and building infrastructure has been completely transformed by the incorporation of Computational Fluid Dynamics (CFD) into thermal systems. The optimisation of double-pipe heat exchangers, the use of latent heat storage systems, and the combination of CFD and Building Information Modelling (BIM) for sophisticated simulation in architectural projects are the three related applications examined in this study. Improving simulation accuracy, energy efficiency, and thermal performance are the main goals. Heat exchanger and thermal energy storage system design and optimisation have been completely transformed by the incorporation of Computational Fluid Dynamics (CFD) into thermal systems analysis. This article examines the use of CFD in the analysis of latent heat storage and double pipe heat exchangers, as well as the new trend of integrating CFD with Building Information Modelling (BIM). The study highlights how important these technologies are for improving thermal performance, increasing energy efficiency, and bridging the gap between design and real-world application.
Keywords: BIM-CFD Integration; flow simulation; infrastructure design optimization; thermal performance integration